Botulinum toxin type A alleviates neuropathic pain and suppresses inflammatory cytokines release from microglia by targeting TLR2/MyD88 and SNAP23 - Wang, Xuan (Cell Biosci, 2020)
BACKGROUND: Botulinum toxin type A (BTX-A) was considered to be a new potential drug for neuropathic pain (NP) treatment. RESULTS: In vivo, BTX-A attenuated chronic compression injury (CCI)-induced pain in rats, and reduced production of pro-inflammatory factors. The inhibition of BTX-A to expression and phosphorylation of SNAP23 were partly reversed by TLR2/MyD88 upregulation. In LPS-stimulated microglia, we also found that BTX-A suppressed TLR2, MyD88, p-SNAP23 and SNAP23 expression, and reduced pro-inflammatory factors secretion. Upregulation of TLR2 and MyD88 recued the inhibition of BTX-A to LPS-induced activation of SNAP23. Then, we demonstrated that BTX-A reduced expression of SNAP23 through inhibition of IKKα/β phosphorylation. Besides, the inhibition of BTX-A to LPS-induced upregulation of SNAP23 can be reversed by proteasome inhibitor. NEDD4, an E3 ubiquitin ligase, was proved to be bind with SNAP23. BTX-A reduced expression of SNAP23 via facilitating ubiquitin-mediated degradation of SNAP23. CONCLUSION: Overall, our data demonstrated that BTX-A attenuated NP via reducing the secretion of pro-inflammatory factors from microglia by inhibition of TLR2/MyD88 signaling. BTX-A downregulated expression of SNAP23 via reducing phosphorylation of IKKα/β, and enhancing ubiquitination of SNAP23 by suppressing TLR2/MyD88 signaling.